Physical properties of undisturbed tropical peat soil at Pekan district, Pahang, west Malaysia - Wahab, Abdul; Hasan, Muzamir; Mohd Kusin, Faradiella; Embong, Zaidi; Uz Zaman, Qamar; Babar, Zaheer Uddin; Imran, Muhammad Syamsul (Penerbit UTHM, 2022)
Peat soilare considered soft soilwith havingweakcharacteristicssuch as low shear strength, high moisture content, and compressibility. Construction perspective, peat soilis consideredas unstable soil due to its poor engineering properties. It may cause an extensive loss in road orbuilding construction projects. Thekey objectives of the current study areto examinethe physical properties of peat soil including shear strength, liquidlimit, moisturecontent, organic content, pH, and dry densityof peat soil inPekandistrict.The peatsamples were collected fromKampung Bahru(KB), Kampung Lancing I(KLI), and Kampung LancingII (KL II), Pekan District, Pahang, Malaysia. Thefinding indicates that the shear strength (kPa) for was measured in between 7.2 to 8.2 kPa. The water content was recorded 537.10%to635.28%. The liquid limit was examined 137.638%to 152.540 %, themaximum drydensity wasexamined6.68 x 10-7kg/cm3to 7.99x 10-7kg/cm3. Theaverage organic content was calculated as approximately 95.88 % to98.48 %. In comparisonwith previous study,its indicatedthat the investigatedpeat soil in Pekan area is mainlycontent with lower shearstrength, highwater content, liquid limit, and low density, resulting in low strengthening properties. Based on the examined physical properties, its specifiedthat peat did not have adequate stability as a road or building foundation.Strengthenof peat are highlyrecommendedfor any types of construction onpeatlandin Pekan district, Pahang, Malaysia.